The leaf architecture and its taxonomic significance in Capparaceae from Egypt - Abd El-Ghani, Monier M.; Kamel, Wafaa; El-Bous, Mona (Acta Biologica Szegediensis, 2007)
The paper deals with the leaf architecture of 19 species belonging to 7 genera (Capparis, Cadaba, Boscia, Maerua, Dipterygium, Cleome and Gynandropsis) of the family Capparaceae sensu lato (including Cleomaceae) from Egypt. A comprehensive description of leaf architecture for the studied taxa was provided, including venation pattern, areolation, and marginal ultimate venation. The venation pattern showed mostly pinnate brochidodromous or craspidododromous. Aeroles may be well or poorly developed. Taxonomically significant leaf features of the examined taxa showed great diversity in leaf or leaflet form, leaf surface, leaf base, leaf persistence, main venation pattern, secondary vein angle, inter secondary veins, number of veins on either side of midrib, free ending ultimate veins and marginal ultimate venation. A new free ending ultimate venation (F.E.V.S) branched with swollen ends was reported. On the basis of leaf architecture, we advocate the recognition of two separate families Capparaceae sensu lato and Cleomaceae. Multivariate analysis was carried out with the aim of solving some of the taxonomic problems existing in the family using 21 characters including 74 character states. Based on the comparison of leaf architecture, we supported the taxonomic treatment of the family Capparaceae. We supported retaining Gynandropsis gynandra as Cleome gynandra of the family Capparaceae, as it clearly nested within Cleome. Leaf architecture helped to distinguish all the species investigated and accordingly a key was provided for this purpose.